Comprehensive omic characterization of breast cancer in Mexican-Hispanic women - Sandra L. Romero-Cordoba (Nature Portfolio, 2021)
Cancers in different populations have been shown to be genetically distinct. Here, the authors sequence breast cancers from Mexican-Hispanic patients and find that these patients have a higher percentage of Akt1 mutations compared to Caucasian and Asian populations, suggesting these are clinically actionable.